The popular sound object and its role in electroacoustic composition. Analysis of expressions of popular music in the electroacoustic repertoire and its use in musical creation (2016)
The academic composition has always looked for ways to nourish the music of popular tradition and it is possible to trace, in the history of Western music, many composers who have resorted to their use. It is important to continue observing and studying the creative processes that keep both musical practices alive and artistic expressions that continue to explore different ways of establishing relationships between academics and the popular. My intention is to show different ways to include sound elements that make reference to popular music or contexts in the composition of electroacoustic music and see its impact on musical discourse. Categories will be established for the identification and analysis of what I will call 'popular sound object' and the way in which it has been used and manipulated by different composers in Latin America and, in particular, in Colombia will be noted.